GENDER AND AGE IDENTIFICATION IN PHRASEOLOGICAL UNITS: THE INTERCONNECTION OF LANGUAGE AND CULTURE. (Scientific journal of the Fergana State University, 2025)
This article analyzes how phraseological units related to gender and age are reflected through culture and language in various linguistic systems. Phraseological expressions are viewed as an important tool for representing cultural stereotypes, social perceptions, and national traditions. The study explores the semantic and pragmatic features of the concepts of gender and age within phraseological units. Additionally, it demonstrates how phraseological expressions reflect the social and cultural views of a nation through the interplay of language and culture.Phraseological units reveal deep cultural layers, illustrating how the historical experiences, religious beliefs, and social customs of a nation are embedded in language. These units play a significant role in national identification and understanding cultural uniqueness. The article also examines the cultural characteristics of phraseological units in German and Uzbek languages and their differences through a comparative analysis. This analysis highlights the inseparable link between language and culture, offering deeper insights into national identity through phraseological expressions.The article extensively addresses the social impact of gender and age stereotypes, their manifestation in national cultures, and their interpretation through semantic analysis of phraseological units. The study also highlights the communicative function of phraseological expressions and their role in cultural interaction between social groups and genders. The synthesis of linguistic and cultural methodologies leads to intriguing conclusions in this field.